Peran Gereja Dalam Memperkuat Iman Jemaat: Strategi Mencegah Pemurtadan Di Era Modern - John Abraham Christiaan; Simon Simon (Sekolah Tinggi Teologi Ekumene Jakarta., 2024)
The rise of Christians apostasy to other religions underlies the researcher to conduct this research. The method used in this study is qualitative descriptive where the research report contains data citations from manuscripts, interviews, field notes, videos, personal documents, notes or other official documents to find the truth in answering this research. The finding of this study is that apostasy occurs because the theological understanding of Christians is not deep. The strategy to prevent such apostasy is that the church must utilize technology as a means for understanding the Christian faith, carry out pastoral and pastoral care to the congregation seriously, as well as monitor contemporary issues that arise through social media that attack the Christian faith in an improper way, then conduct studies and provide the congregation with a correct theological understanding, the church can also use social media to convey true Christian teachings so that the Christian congregation can know the true teachings to ward off the heresy that leads to apostasy.